1982
DOI: 10.1039/p29820000355
|View full text |Cite
|
Sign up to set email alerts
|

13C and15N nuclear magnetic resonance spectra of Meisenheimer complexes of 1,3,5-trinitrobenzene

Abstract: Czec hosl ova ki a 13C and l5N n.m.r. spectra (at the natural abundance level of l5N) have been measured and interpreted for the Meisenheimer complexes (I)-(XII) of 1.3,5-trinitrobenzene (TNB) with anions of cyclopentanone, cyclohexanone, cycloheptanone, acetone, dimethyl malonate, methyl cyanoacetate, methyl acetoacetate, pentane-2,4-dione, 3-methylpentane-2,4-dione, phenol, and methanol. 3C N.m.r. spectra of the corresponding carbon-acids have been measured in [2HG]DMS0. The complexes derived from ketones an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The Δδ(H) values lie in the range −0.61, −0.79 ppm, comparing well with the proton shifts observed in the ionization of various 2,4,6-trinitrobenzyl derivatives, including 2,4,6-trinitrotoluene (TNT) (Δδ(H 3,5 ) = −0.74 ppm), , (3) the resonances of the C 2,6 and C 4 carbons, especially the latter, move markedly to high field, whereas those of the C 3,5 carbons move slightly to low field on going from 3a−c to C-3a−c : Δδ(C 2,6 ) ≈ −10; Δδ(C 4 ) ≈ −18; Δδ(C 3,5 ) ≈ +1. Interestingly, the situation is reminiscent of the one reported in 13 C studies of the formation of the related carbanion C-5 of 2,4,6-trinitrophenylacetone as well as of that of picryl σ-adducts of general structure 5 according to eq 9. In these latter instances, SCFMO calculations have indicated that the σ-complexation results in increases in π-electron density at the 2, 4, and 6-ring positions as well as on the NO 2 substituents and in decreases at the 3- and 5-positions, accounting well for the observed variations in the carbon chemical shifts of the cyclohexadienyl ring: Δδ(C 2,6 ) ≈ −17, Δδ(C 4 ) ≈ −29, Δδ(C 3,5 ) ≈ 2. , In addition, the calculations confirmed the major role of the paraquinoid structure 6B in the delocalization of the negative charge of the adducts…”
Section: Discussionmentioning
confidence: 71%
“…The Δδ(H) values lie in the range −0.61, −0.79 ppm, comparing well with the proton shifts observed in the ionization of various 2,4,6-trinitrobenzyl derivatives, including 2,4,6-trinitrotoluene (TNT) (Δδ(H 3,5 ) = −0.74 ppm), , (3) the resonances of the C 2,6 and C 4 carbons, especially the latter, move markedly to high field, whereas those of the C 3,5 carbons move slightly to low field on going from 3a−c to C-3a−c : Δδ(C 2,6 ) ≈ −10; Δδ(C 4 ) ≈ −18; Δδ(C 3,5 ) ≈ +1. Interestingly, the situation is reminiscent of the one reported in 13 C studies of the formation of the related carbanion C-5 of 2,4,6-trinitrophenylacetone as well as of that of picryl σ-adducts of general structure 5 according to eq 9. In these latter instances, SCFMO calculations have indicated that the σ-complexation results in increases in π-electron density at the 2, 4, and 6-ring positions as well as on the NO 2 substituents and in decreases at the 3- and 5-positions, accounting well for the observed variations in the carbon chemical shifts of the cyclohexadienyl ring: Δδ(C 2,6 ) ≈ −17, Δδ(C 4 ) ≈ −29, Δδ(C 3,5 ) ≈ 2. , In addition, the calculations confirmed the major role of the paraquinoid structure 6B in the delocalization of the negative charge of the adducts…”
Section: Discussionmentioning
confidence: 71%
“…Triethylammonium 1-acetonyl [ 17 O]-2,4,6-trinitrocyclohexadienide (2). 3 A solution of 0.7 g (3.3 mmol) of [ 17 O]-1,3,5-trinitrobenzene in ca 5 ml of dry acetone was added to 0.6 g (0.83 ml, 6 mmol) of triethylamine. After several minutes, the adduct was precipitated by addition of dry diethyl ether (ca 100 ml).…”
Section: Preparation Of Meisenheimer Adductsmentioning
confidence: 99%
“…1 H NMR spectroscopy is the most widely used and reliable technique for investigating the structure and the reactivity of anionic σ complexes,16 as well as 13 C and 15 N NMR spectroscopy, which have only recently been applied to this type of compound 17. Stopped‐flow (SF) and temperature‐jump (TJ) are additional techniques that have been frequently employed 18.…”
Section: Introductionmentioning
confidence: 99%